Application of Targeted Yield Concept for Efficient and Economic Fertilizer Use for Wheat in Arid Zone of Punjab - Saini, S P (Annals of Arid Zone, 2016)
The validity of the fertilizer adjustment equations was tested by conducting yield target trials with wheat var. PWB 343 for two years at farmers’ fields in Bathinda district. The results indicated that actual yields were 46.1, 51.2, 55.7 and 60.4 q ha’l with target of 45, 50, 55 and 60 q ha’l and when the fertilizers were applied on the basis of soil tests. Thus, the utility of this approach was established for recommending soil-test-based fertilizers for WHeat crop to the farmers. Every kg of applied nutrient produced 26.3, 25.4, 24.4, 21.3 kg of wheat grain for target of 45, 50, 55, 60 q ha’l and (22.4 and 23.2) and (19.4 and 19.8) for STRD and FP, respectively. It clearly pointed out higher fertilizer-use efficiency when fertilizer was applied on the basis of targeted yield concept as compared to farmers’ practices (FP). Moreover target yield approach was found to be superior upto 55 q ha’l target qver FP and soil-lest-based fertilizer recommended dose approach.